Projetos esportivos de caráter social e carreiras desviantes : um estudo de caso com jovens em conflito com a lei - Antunes, Scheila Espindola (2018)
There is a widespread discourse around sport about its potentialities in dealing with ethical and moral values. Embedded in this discourse is a premise that points it as a tool of high potential within social actions aimed at socially disadvantaged publics and communities. The justifications for the insertion of the sport in these actions may be based on the belief in its educational potential, in the (alleged) power to fight crime or in the belief of its potential for the development of social skills and competences. It was based on the debate promoted around these social uses of sport that we delimited as the central objective of the thesis: to analyze the meanings and meanings that deviant young people attribute to the sport from the sports experience enjoyed within a project of social character, seeking to infer if such experience is able to keep these young people from deviant careers. The field research was developed from a qualitative case study, through direct observation, participation and interviews (semi structured and non directive) with 04 deviant youths participating in a social sport project in the city of Barbacena/MG. The analyzes indicate that participation in the sports project did not promote perceptible changes in the ways of thinking and acting of the deviants, no changes was promoted in their individual projects too. For three of the youths followed in the study, the sporting practices of the project served only as a strategy to alleviate the boredom caused by the socio-educational measure. Thus, it can not be said that participation in the social project has contributed to distancing these youths from possible deviant careers